Supervising in Silence: Challenges and Coping Strategies in EFL Undergraduate Thesis Supervision in Indonesia - Mukhlash Abrar; Failasofah Failasofah; Sanggarini Naomi; Nunung Fajaryani; Masbirorotni Masbirorotni (AL-ISHLAH: Jurnal Pendidikan, 2025)
Undergraduate thesis supervision plays a critical role in shaping students' academic success, particularly in English as a Foreign Language (EFL) contexts. However, supervising EFL students poses various challenges for lecturers, often impacting the quality and progress of student research. This qualitative case study explores the experiences of eight lecturers supervising undergraduate theses in an English education program at a public university in Jambi, Indonesia. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis following Braun and Clarke's (2006) six-phase framework. Findings reveal two major categories of challenges: internal and external. Internal challenges include time constraints due to heavy workloads and mismatches between supervisors’ expertise and student research topics. External challenges involve student disengagement, poor writing skills, limited progress, low motivation, and external personal issues. To address these, lecturers employed three main strategies: (1) self-management (scheduling supervision, learning new content areas), (2) assistance (giving direction, motivation, and written corrective feedback), and (3) communication and technological support (maintaining regular contact and using online platforms for supervision). The study highlights the complex dynamics of thesis supervision in EFL contexts and the proactive efforts of lecturers to navigate these challenges. The findings underscore the need for institutional support, targeted training, and better supervisor-student alignment to enhance the supervision process and student outcomes.